The three-stage rock failure dynamics of the Drus (Mont Blanc massif, France) since the June 2005 large event - Guerin, Antoine; Ravanel, Ludovic; Matasci, Battista; Jaboyedoff, Michel; Deline, Philip (Scientific reports, 2020)
Since the end of the Little Ice Age, the west face of the Drus (Mont Blanc massif, France) has been affected by a retrogressive erosion dynamic marked by large rockfall events. From the 1950s onwards, the rock failure frequency gradually increased until the large rockfall event (292,680 m 3 ) of June 2005, which made the Bonatti Pillar disappear. Aiming to characterize the rock failure activity following this major event, which may be related to permafrost warming, the granitic rock face was scanned each autumn between October 2005 and September 2016 using medium- and long-range terrestrial laser scanners. All the point clouds were successively compared to establish a rockfall source inventory and determine a volume-frequency relationship. Eleven years of monitoring revealed a phase of rock failure activity decay until September 2008, a destabilization phase between September 2008 and November 2011, and a new phase of rock failure activity decay from November 2011 to September 2016. The destabilization phase was marked by three major rockfall events covering a total volume of 61,494 m 3 , resulting in the progressive collapse of a new pillar located in the northern part of the June 2005 rockfall scar. In the same way as for the Bonatti Pillar, rock failure instability propagated upward with increasing volumes. In addition to these major events, 304 rockfall sources ranging from 0.002 to 476 m 3 were detected between 2005 and 2016. The temporal evolution of rock failure activity reveals that after a major event, the number of rockfall sources and the eroded volume both follow a rapid decrease. The rock failure activity is characterized by an exponential decay during the period following the major event and by a power-law decay for the eroded volume. The power law describing the distribution of the source volumes detected between 2005 and 2016 indicates an exponent of 0.48 and an average rock failure activity larger of more than six events larger than 1 m 3 per year. Over the 1905–2016 period, a total of 426,611 m 3 of rock collapsed from the Drus west face, indicating a very high rock wall retreat rate of 14.4 mm year −1 over a surface of 266,700 m 2 . Averaged over a time window of 1000 years, the long-term retreat rate derived from the frequency density integration of rock failure volumes is 2.9 mm year −1 . Despite difficulty in accessing and monitoring the site, our study demonstrates that long-term surveys of high-elevation rock faces are possible and provide valuable information that helps improve our understanding of landscape evolution in mountainous settings subject to permafrost warming.